Study on the selection criteria for choosing domestic package tours in Malaysia [electronic resource] - Zainab Khalifah, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Perancangan Pelancongan)) - Universiti Teknologi Malaysia, 2007